Pengaruh Komunikasi Internal Terhadap Motivasi Volunteer Masjid Nurul Asri Mengalirkan Energi Kebaikan - Herera Savitri, Ayu; Pungki Refani, Meita; Juwanti, Susi (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Internal communication plays an important role in building volunteer motivation in community-based organizations, including mosques. This study aims to analyze the effect of internal communication on the motivation of volunteers at Nurul Ashri Mosque in implementing the “Flowing Good Energy” program. Using a quantitative approach, this study involved 50 volunteers who actively participated in the program. Data were collected through questionnaires and analyzed using a simple linear regression method. The results showed that internal communication had a significant influence on volunteer motivation, with a contribution of 65%. The recommendation from this study is to improve the quality of internal communication through training, the use of effective communication media, and routine evaluations to support the sustainability of volunteer motivation.